The Influence of Work Life Balance on Employee Loyalty in Companies - Renaldy Andriannoor; Wisnu Panggah Setiyono; Sriyono Sriyono (Dinasti Publisher, 2025)
In the contemporary era characterized by globalization and accelerated technological advancement, work-life balance has become an important issue faced by companies in maintaining employee performance and loyalty. An imbalance between the demands of work and personal life can have a negative impact on employee well-being and affect productivity levels and job satisfaction. Therefore, this study aims to examine the effect of work-life balance on employee loyalty, as well as to explore the factors that influence the relationship. This study aims to analyze the extent to which work-life balance policies implemented by companies can increase employee loyalty. This research also aims to identify policies and best practices that can be implemented to create an effective work-life balance. This research employs a quantitative approach with data collection through a survey involving 175 employees from the electricity, energy, and service sectors at PLN Indonesia Power UBP Asam-Asam. The collected data will be analyzed using simple linear regression techniques to test the relationship between work-life balance and employee loyalty. Additionally, descriptive analysis will be used to describe the demographic characteristics of the respondents and the company's work-life balance policies.